A study of the relative velocities of small particles that are orbiting the earth - Celestino, Claudia C.; Winter, Othon C. [UNESP]; De A. Prado, Antonio F.B. (My University, 2008)
The evolution of the velocity of the particles with respect to the circular orbits of satellites that are around the Earth that the particles will cross, suggests a range of possible velocities of impact as a function of the altitude of the satellite. A study made from those results show that the maximum relative velocities occur at the semi-latus rectum, independent of the initial semi-major axis of the particle. Considering both the solar radiation pressure and the oblateness of the Earth, it is visible that a precession in the orbit occurs and there is also a variation in the eccentricity of the particle as a function of its orbital region and its size. This is important information, because the damage caused in a spacecraft depends on the impact velocity.
Keywords: Circular orbits; Impact velocities; Oblateness; Relative velocities; Semi-major axis; Small particles; Solar radiation pressures; Orbits; Probability density function; Space flight; Sun; Velocity; Mechanics